(E)-1-Phenyl-2-({5-[(1E)-(2-phenylhydrazin-1-ylidene)methyl]-2-thieny l}methylidene)hydrazine - de Lima, G.M.; Harrison, W.T.A.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
The title molecule, C18H16N4S, adopts a U-shape with the aromatic groups lying syn and orientated in the same direction as the thiophene S atom. The conformation about each of the C = N bonds is E. Overall, the molecule is curved as seen in the dihedral angle of 30.26 (19)degrees formed between the terminal benzene rings. In the crystal, supramolecular chains along the c axis are formed by a combination of N-H center dot center dot center dot N hydrogen bonds and N-H center dot center dot center dot pi interactions.